Conversor de fator de potência verdadeiramente unitário como inversor central em geração fotovoltaica - Marcos Henrique da Silva Alves (2020)
The massive use of converters in electrical power systems has benefits as diverse as their purposes. A commonly verified limitation is associated with the amount of residual harmonics that the converters inject into the network. A wide niche of applications is connected to this class of converters, such as direct current energy transmission, electrical drives, electrical traction, switching sources and so on. Although much research has been carried out aiming to develop high-power converters for grid connection (in english, grid-tied), composed of several small power modules connected to smaller strings in order to improve the extraction of energy available in solar modules, central inverters they still constitute the most used solution in solar energy plants, mainly due to their low cost and complexity, as well as high reliability when there is a redundancy of keys. Most of these converters use passive filters on the network side in order to comply with the power quality restrictions and requirements of the country network codes and recommended international standards. In summary, these filters contain a combination of inductors and capacitors that can be a source of resonances for the system, in addition to contributing to many problems for which they were installed for the purpose of prevention. Recently, a truly unitary power factor converter (from English True Unity Power Factor - TUPF) was proposed as an alternative to traditional solutions, which indeed have limitations for their mass use. In this context, the TUPF converter is proposed as a grid-tied solution for high powers that provides sinusoidal currents from the normative perspective, without capacitive elements or passive filters when connecting to the network, switching at low frequencies, as well as the use of transformers and topology conventional converters. When it comes to solar application, TUPF has the advantage of not needing a boost converter to implement the MPPT algorithm. This translates into greater reliability, as it is a less energy processing stage, leading to less chance of failure and greater efficiency. The main contribution of this work refers to the presentation of the TUPF converter as a central inverter suitable for solar photovoltaic applications in the situation where the DC voltage and the modulation index need to be continuously modified according to the reference of a maximum power tracking algorithm (MPPT, from Maximum Power Point Tracking), which differs from the applications previously presented, in which the DC voltage reference is a constant constant value. Finally, it is presented, for the first time, closed-loop results on a HIL test bench, as well as the startup of the first TUPF prototype, making use of the energy generated by the Tesla photovoltaic solar plant.